Music, Cognition, and Computerized Sound: An Introduction to Psychoacoustics - Cook, Perry R. (Cambridge, MA MIT Press, 2001)
How hearing works and how the brain processes sounds entering the ear to provide the listener with useful information are of great interest to psychologists, cognitive scientists, and musicians. However, while a number of books have concentrated on individual aspects of this field, known as psychoacoustics, there has been no comprehensive introductory coverage of the multiple topics encompassed under the term. Music, Cognition, and Computerized Sound is the first book to provide that coverage, and it does so via a unique and useful approach.The book begins with introductory chapters on the basic physiology and functions of the ear and auditory sections of the brain, then proceeds to discuss numerous topics associated with the study of psychoacoustics, including cognitive psychology and the physics of sound. The book has a particular emphasis on music and computerized sound. An accompanying audio CD includes many sound examples to help explicate the text.The contributing authors include John Chowning, Perry R. Cook, Brent Gillespie, Daniel J. Levitin, Max Mathews, John Pierce, and Roger Shepard.
Keywords: Music psychology